2016
DOI: 10.1128/jvi.01559-16
|View full text |Cite
|
Sign up to set email alerts
|

The Glycosylphosphatidylinositol-Anchored Variable Region of Llama Heavy Chain-Only Antibody JM4 Efficiently Blocks both Cell-Free and T Cell-T Cell Transmission of Human Immunodeficiency Virus Type 1

Abstract: The variable regions (VHHs) of two heavy chain-only antibodies, JM2 and JM4, from llamas that have been immunized with a trimeric gp140 bound to a CD4 mimic have been recently isolated (here referred to as VHH JM2 and VHH JM4, respectively). JM2 binds the CD4-binding site of gp120 and neutralizes HIV-1 strains from subtypes B, C, and G. JM4 binds gp120 and neutralizes HIV-1 strains from subtypes A, B, C, A/E, and G in a CD4-dependent manner. In the present study, we constructed glycosylphosphatidylinositol (GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Our past studies of anti-HIV Env GPI-anchor antibody derivatives have shown increased potency and breadth of neutralization of HIV-1 compared to levels of their secreted counterparts (28)(29)(30)(31)33). In those studies, we demonstrated that anti-HIV Env GPI-anchored antibody derivatives severely restrict viral replication at the level of entry.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our past studies of anti-HIV Env GPI-anchor antibody derivatives have shown increased potency and breadth of neutralization of HIV-1 compared to levels of their secreted counterparts (28)(29)(30)(31)33). In those studies, we demonstrated that anti-HIV Env GPI-anchored antibody derivatives severely restrict viral replication at the level of entry.…”
Section: Discussionmentioning
confidence: 91%
“…It is known that CD4, the receptor for HIV-1 entry (25,26), and the HIV Env protein colocalize with polarized raft markers GM1 and CD59 but not with transferrin receptor, which is excluded from lipid rafts (27). Previously, we showed that binding regions of anti-HIV Env monoclonal antibodies, such as single-chain Fv (scFv) (28), the heavy-chain complementarity-determining region 3 (HCDR3) of PG16, which binds a linear epitope on the HIV-1 Env (29), llama single-chain (30) antibodies, or even the C34 peptide of the HIV Env gp41 protein (31), can be targeted to lipid rafts by genetically linking them to a glycosyl-phosphatidylinositol (GPI) attachment signal from decay-accelerating factor (DAF) (32). Interestingly, when these molecules are targeted to the lipid raft using a GPI anchor, they exhibited potent neutralizing activity, blocking entry of different HIV-1 subtypes and variants in both cell-free infection and cell-cell transmission assays (28)(29)(30)(31)33).…”
mentioning
confidence: 99%
“…Further, Liu et al developed GPI-anchored variable regions by genetically linking sdAbs with a glycosylphosphatidylinositol (GPI) attachment signal, which targeted lipid rafts of plasma membrane. Transduction of human CD4 + cell lines and primary CD4 T cells with GPI-VHH JM4 conferred broad and potent neutralization of HIV-1 and efficiently interfered with cell-cell transmission of HIV-1 and HIV-1 envelope-mediated fusion ( 76 ). One extremely potent and broad HIV-1-neutralizing sdAb from an immunized llama, J3, targeted the CD4-binding site and neutralized 96% of all strains tested ( 11 ).…”
Section: Sdabs As Potential Therapeutics Against Virusesmentioning
confidence: 99%
“…In addition, it is possible that the binding of BiIA-SG Hu5A8 domains to CD4 increases the local concentration of PGT128 near the cell membrane for enhanced HIV-1 neutralization. This mechanism is possible because antibody membrane anchoring can increase neutralizing activities of both bnAbs and nonneutralizing anti-HIV antibodies (55,56). Future structural analysis of BiIA-SG is necessary to answer its mode of action.…”
Section: Discussionmentioning
confidence: 99%